Oil and Growth in Transition Countries - Christa N. Brunnschweiler (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
This paper examines the impact of oil on economic growth in transition economies of the former Soviet Union (FSU) and Central and Eastern Europe (CEE). We use oil production and reserves data in a series of panel estimations to show that oil has had strong and robust positive growth effects between 1990-2006. This is confirmed when we consider the different oil ownership structures. Additionally, we find that privatization levels have had positive growth effects, while privatization speed has had negative effects on growth.
Keywords: Q32; O40; O13; P28; 330; oil; resource curse; economic growth; transition countries; oil ownership; Erdölvorkommen; Mineralölwirtschaft; Privatisierung; Systemtransformation; Wirtschaftswachstum; Transformationsstaaten